Peranan Pendidikan Akhlak dalam Mengembangkan Kepribadian Peserta Didik di Madrasah Aliyah Negeri 1 Parepare - Djamaluddin M Idris; Usman Usman (Madrasah Tsanawiyah DDI Cilellang, 2019)
The purpose of this study was to analyze the role of moral education in developing the personality of students in Madrasah Aliyah Negeri 1 Parepare which focused on 1) the implementation of moral education in developing the personality of students; 2) contribution of moral education in developing the personality of students; and 3) supporting and inhibiting factors to the implementation of moral education in developing the personality of students. This type of research is qualitative. The source of the data came from respondents consisting of faith-moral (akidah akhlak) teachers and some students from Madrasah Aliyah Negeri 1 Parepare. Data are collected through observation, interviews, and documentation. Then analyzed through three stages: data reduction, data display, and conclusion. The results showed that the implementation of moral education in Madrasah Aliyah Negeri 1 Parepare uses two forms of learning, namely classroom learning and learning outside the classroom. The contributions of moral education in developing the personality of students are 1) as a filter of negative influences from outside and 2) as fostering students’ faith and moral values so that they determine their attitudes and behavior. Supporting factors for the implementation of moral education in developing the personality of students in the Madrasah Aliyah Negeri 1 Parepare are 1) professional teaching staff; 2) good cooperation from all stakeholders; 3) facilities and infrastructure. The inhibiting factors are 1) lack of religious education in the family and attention from parents; 2) heterogeneity of environmental conditions of students; and 3) lack of awareness of students.